Ultra high molecular weight polyethylene/graphene oxide nanocomposites: Thermal, mechanical and wettability characterisation. (1st September 2015) - Suñer, S.; Joffe, R.; Tipper, J.L.; Emami, N.
Abstract: Numerous carbon nanostructures have been investigated in the last years due to their excellent mechanical properties. In this work, the effect of the addition of graphene oxide (GO) nanoparticles to UHMWPE and the optimal %wt GO addition were investigated. UHMWPE/GO nanocomposites with different GO wt% contents were prepared and their mechanical, thermal, structural and wettability properties were investigated and compared with virgin UHMWPE. The results showed that the thermal stability, oxidative resistance, mechanical properties and wettability properties of UHMWPE were enhanced due to the addition of GO. UHMWPE/GO materials prepared with up to 0.5 wt% GO exhibited improved characteristics compared to virgin UHMWPE and nanocomposites prepared with higher GO contents.